21. INTRAOPERATIVE CONTINUOUS RENAL REPLACEMENT THERAPY DURING LIVER TRANSPLANTATION: 2 CASE STUDIES OF LIVER TRANSPLANTATION AT VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objects: Clinical report on the effectiveness of continuous renal replacement therapy in liver transplantation in patients with indications for liver transplantation and renal impairment.Materials and methods: Retrospective study from December 2019 to July 2024, describing cases of liver transplantation in patients with liver failure accompanied by stage IV-V kidney damage, using continuous hemodialysis during surgery.Results: There were 2 patients with liver and kidney failure who received liver transplantations, of which 1 patient received simultaneous liver and kidney transplantations, both of whom received continuous hemodialysis during surgery: the first patient had liver failure, with stage V kidney failure, received simultaneous liver and kidney transplantations, using CVVH and the second patient had liver failure, with stage IV kidney failure, received liver transplantation and used CVVHDF. During surgery, both patients had stable developments with vital signs, water and electrolyte balance, and acid-base balance. However, after surgery, the 1st patient was discharged from the hospital, in stable condition with normal liver and kidney function, while the 2nd patient had complications of bile leakage on the 10th day, was re-operated and still had to be treated in the intensive care unit.Conclusion: Continuous renal replacement therapy may be used in liver transplantation in patients with end-stage liver disease who have renal dysfunction, with the goal of optimizing the electrolyte and acid-base balance induced by the surgery.
Keywords: Liver transplantation; liver failure; kidney failure; continuous renal replacement therapy